2021
DOI: 10.1038/s41579-021-00540-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis biofilm formation and social interactions

Abstract: Biofilm formation is a process in which microbial cells aggregate to form collectives that are embedded in a self-produced extracellular matrix. Bacillus subtilis is a Gram-positive bacterium that is used to dissect the mechanisms controlling matrix production and the subsequent transition from a motile planktonic cell state to a sessile biofilm state. The collective nature of life in a biofilm allows emergent properties to manifest, and B. subtilis biofilms are linked with novel industrial uses as well as pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
232
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 303 publications
(237 citation statements)
references
References 160 publications
(263 reference statements)
4
232
0
1
Order By: Relevance
“…Theoretical models on surface growth are paralleled by a large body of empirical literature where surface-associated organisms are studied by either growing collectives in isolation (e.g., biofilms, colonies, pellicles, swarms, fruiting bodies) [110][111][112][113], thereby focusing on their multicellular organization [36,[114][115][116][117][118], or by competing several genotypes against each other on a surface [30,[119][120][121][122][123][124]. Competition experiments revealed that spatial interactions can strongly affect the outcome of competition, oftentimes leading to the coexistence of multiple genotypes [43,120,125].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical models on surface growth are paralleled by a large body of empirical literature where surface-associated organisms are studied by either growing collectives in isolation (e.g., biofilms, colonies, pellicles, swarms, fruiting bodies) [110][111][112][113], thereby focusing on their multicellular organization [36,[114][115][116][117][118], or by competing several genotypes against each other on a surface [30,[119][120][121][122][123][124]. Competition experiments revealed that spatial interactions can strongly affect the outcome of competition, oftentimes leading to the coexistence of multiple genotypes [43,120,125].…”
Section: Discussionmentioning
confidence: 99%
“…The PGPR B. subtilis is a promising sustainable alternative to traditionally used agrochemicals, as it harbors many important plant growth-promoting and biocontrol properties while having reduced negative effects on biodiversity and the environment (Blake et al ., 2021; Arnaouteli et al ., 2021). Even though its potential seems immense under laboratory conditions and in greenhouse trials, the success varies greatly when applied in fields (Peng et al ., 2011; Bardin et al ., 2015; Moreira & de Mio, 2015; Wei et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Matrix production is well known to be required for the formation of architecturally complex biofilms under laboratory conditions (Arnaouteli et al, 2021; Branda et al, 2006). Moreover, matrix production and localized cell death are responsible for the formation of wrinkles during biofilm development (Asally et al, 2012; Branda et al, 2006; Gallegos‐Monterrosa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The variation in environmental conditions throughout the biofilm (Costerton et al, 1994) thereby leads to a heterogeneous population with different cell types performing distinct tasks and occupying different micro‐niches. The extracellular signals triggering cell differentiation include quorum‐sensing molecules, natural products, and nutrient availability that activate a set of sensor kinases (Arnaouteli et al, 2021; Mhatre et al, 2014). Once activated, the sensor kinases phosphorylate their respective master transcriptional regulators, Spo0A, DegU, and ComA, each of which activates different sets of genes (López & Kolter, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation